Synthesis and melt processing of cellulose esters for preparation of thermoforming materials and extended drug release tablets. (1st December 2017) - Virtanen, Sanna; Talja, Riku; Vuoti, Sauli
Highlights: Sequential esterification improved the thermal processability of cellulose without the use of external plasticisers. Appropriate degree of substitution and position of short-chain substituents improved the mechanical properties of cellulose esters. Sequentially esterified cellulose hexanoate-acetate showed potential for melt spinning. Cellulose hexanoate-acetate ester showed potential for the preparation of multi-unit pellet systems for controlled delivery of three water-insoluble drugs. Abstract: Using softwood pulp as the starting material, the synthesis of regioselectively substituted mixed cellulose esters with varying degree of substitution and ratio of short/long chains was successfully completed. The structures of the cellulose esters were characterised. The impact of the structural changes and the degree of substitution of the cellulose esters on thermal properties and processability were investigated. The study shows that the sequential esterification is a promising modification route for cellulose to improve its thermal processability and mechanical properties without the use of external processing aids such as plasticisers. In particular, the hexanoate group in the C6 position on the cellulose backbone acts as an internal plasticiser and improves thermal processability and increases the strength and stiffness of the cellulose ester. The properties of sequentially esterified cellulose promote its practical use in plastics, coatings, films and drug delivery. Sequentially esterified cellulose hexanoate-acetate was used successfully in a coating formulation for the preparation of tablets and showed a stable extended release profile for three water-insoluble drugs in this context. The pH of the release medium had no notable effect on the release properties.